FRI0179 Minimal to no transfer of certolizumab pegol into breast milk: results from cradle, a prospective, postmarketing, multicenter, pharmacokinetic study. (15th June 2017) - Clowse, MEB; Förger, F; Hwang, C; Thorp, J; Dolhain, RJEM; Tubergen, A van; Shaughnessy, L; Simpson, J; Teil, M; Toublanc, N; Wang, M; Hale, TW
Abstract : Background: Women with active chronic rheumatic inflammatory conditions (RA, PsA, AxSpA) often face uncertainty regarding the safety of the use of biologics during breastfeeding. 1 Limited and non-validated data exist on the potential transfer of anti-TNFs into breast milk. 2 CRADLE (NCT02154425 ) was the first sponsored study to evaluate certolizumab pegol (CZP) concentrations in breast milk, and to estimate the Average Daily Infant Dose (ADID) of maternal CZP. Objectives: To determine the concentration of CZP in breast milk and calculate the ADID of maternal CZP. Methods: CRADLE was a pharmacokinetic study of lactating mothers (≥6 weeks postpartum) receiving commercial CZP. Decision to treat with CZP and breastfeed was independent of study participation. At steady state (≥3 CZP doses), breast milk samples were collected on Days 0, 2, 4, 6, 8, 10, 12, 14 (±28) from each mother across 1 dosing period. CZP was detected using a highly sensitive, CZP-specific electrochemiluminescence immunoassay validated in milk (lower limit of quantification [LLOQ]=0.032 μg/mL; 10-fold lower than previous assays). CZP stability in milk was confirmed. Results: 18 CZP-treated mothers were screened: 17 entered the sampling period; 16 on CZP 200 mg Q2W; 1 on CZP 400 mg Q4W (7 RA; 5 SpA; 5 CD; Table A). Samples from 4/17 mothers had no measurable CZP in breast milk; 13/17 had quantifiable levels for at least 1 time point (highest concentration: 0.076 μg/mL; Table B). Estimated ADID ranged 0–0.0104 mg/kg/day; median Relative Infant Dose (RID; calculated post hoc 3 ): 0.15%. Infants of CZP-exposed mothers had a safety profile consisting of events occurring in unexposed infants of similar age. Conclusions: CZP was below the lower limit of quantification in 56% of the milk samples. When detectable, CZP concentrations were less than 3x LLOQ (<1% of expected plasma concentration of a therapeutic dose 4 ), indicating no to minimal transfer of CZP from plasma to breast milk. RID was below 0.5% of maternal dose; <10% is unlikely to be of clinical concern. 3 CZP absorption via breast milk is unlikely, due to low bioavailability and its Fc-free molecular structure. These findings support continuation of CZP treatment during breastfeeding. References: Götestam Skorpen C. Ann Rheum Dis 2016;75:795–810. Ben-Horin S. J Crohns Colitis 2011;5:555–8. Hale TW. Textbook of Human Lactation. Amarillo, TX: Hale Publishing, 2007. Lacroix BD. Gastroenterology 2010;138:S163–4. Acknowledgements: This study was funded by UCB Pharma. We are indebted to the mothers and their infants for their altruistic participation. We thank the nurses, investigator teams and Nicole Hurst, PPD, and acknowledge Amanda Golembesky and Gerry Parker, UCB Pharma. Editorial services were provided by Costello Medical Consulting. Disclosure of Interest: M. Clowse Grant/research support from: Pfizer, Janssen, Consultant for: UCB Pharma, F. Förger Grant/research support from: UCB Pharma, Speakers bureau: Mepha, Roche, UCB Pharma, C. Hwang Grant/research support from: AbbVie, UCB Pharma, Consultant for: Janssen, J. Thorp Grant/research support from: UCB Pharma, Consultant for: Genentech/Roche, UCB Pharma, R. Dolhain Grant/research support from: UCB Pharma, A. van Tubergen Grant/research support from: Pfizer, AbbVie, UCB Pharma, Janssen-Cilag, Celgene, Novartis, MSD, Consultant for: AbbVie, Novartis, Janssen-Cilag, Pfizer, Speakers bureau: MSD, Janssen-Cilag, Pfizer, L. Shaughnessy Employee of: UCB Pharma, J. Simpson Employee of: UCB Pharma, M. Teil Employee of: UCB Pharma, N. Toublanc Employee of: UCB Pharma, M. Wang Employee of: UCB Pharma, T. Hale Consultant for: UCB Pharma